Konflik Kewenangan Antar Lembaga Negara dalam Ketatanegaraan Indonesia - Fadan Buljah Alaryahiyyah; Muhammad Rifki; Revan Sauqi; Muhammad Bahri; Ade Fartini (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This research aims to analyze the conflict of authority between the Constitutional Court (Mahkamah Konstitusi) and the Supreme Court (Mahkamah Agung) within Indonesia’s constitutional system, focusing on institutional disputes that have emerged following the amendment of the 1945 Constitution. The main objective is to examine the legal foundations, juridical implications, and mechanisms for resolving jurisdictional conflicts between the two courts through a normative juridical approach and case-based analysis. The findings indicate that authority conflicts between the Constitutional Court and the Supreme Court often arise from overlapping legal norms and ambiguities in the delineation of constitutional functions established by the 1945 Constitution and its implementing laws. In several cases, such as disputes over the judicial review of regulations below the level of statutes, divergent interpretations have occurred regarding the scope of constitutional versus administrative jurisdiction. This study reveals that legal harmonization through regulatory reform and inter-institutional coordination is essential to prevent future jurisdictional overlaps. The conclusion emphasizes the need to strengthen the principles of checks and balances and clarify the hierarchy of norms to ensure stability in Indonesia’s constitutional framework. The research recommends the establishment of a cross-institutional constitutional forum as a mediation mechanism among state institutions to uphold constitutional supremacy and legal certainty in Indonesia.